Penyelesaian Sengketa Inggris – Iran Terkait Hak Lintas Damai Kapal Stena Impero - Tetelepta, Joel; Tahamata, Lucia Charlota Octovina; Daties, Dyah Ridhul Airin (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2023)
Introduction: Since World War II the Law of the Sea has undergone many changes along with the times. The United Conference on Trade Development says almost more than 77 percent of international trade is transported by sea. As part of the sea, the strait plays an important role for international trade, one of which is the Strait of Hormuz.Purposes of the Research: To study or analyze how UNCLOS 1982 regulates the Right of Peaceful Passage and examines how the form of settlement of the Stena Impero vessel detention dispute.Methods of the Research: The research method used is normative juridical research, the type of research is analytical descriptive. The sources of legal materials used are primary, secondary and tertiary legal materials. The legal material collection technique used in this research is through library research. Analysis of legal materials is descriptive qualitative.Results of the Research: The research results conclude that the right of innocent passage has been regulated in UNCLOS 1982 Part III concerning Innocent Passage, article 45 paragraphs 1 and 2. Foreign ships that use the right of innocent passage in the territorial sea or waters of a coastal state must follow the regulations in force in that country and, in general, the mechanism of international law in resolving international disputes can be pursued through two channels, namely litigation and non-litigation. In particular, for the settlement of the Stena Impero ship dispute between Britain and Iran, the efforts that can be taken are through litigation, namely through the international court for the law of the sea (Internasional Tribunal for the Law on the Sea)